LA CELEBRACIÓN DE LOS QUINCE AÑOS: UNA VENTANA AL MUNDO SOCIAL Y CULTURAL DE LAS ADOLESCENTES COSTARRICENSES (1951-1971) - Salazar Corrales, Zaira (2008)
The present article describes the main characteristics of the announcements published in the Costa Rican media on occasion of fifteenth birthday celebrations during the period between 1951 and 1971. Based on these publications, the author seeks to determine which social groups used the press as a means to announce their young girl’s fifteenth birthday, analyzing as well the degree of significance this public announcement had on such an event. Finally, the study also aims to establish the geographical location of the domicile of each one of the young girls announced therein.